(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the essence of the term inflation, types of its calculation, theoretical aspects of the inverse relationship between inflation and unemployment and its impact on the economy, and analyzes anti-inflationary policy.